Exploring the Potential for Achieving Self-determined Community Economic Development in Nunavut: An Examination of the Government of Nunavut’s Economic Development Strategies - Carlson, Jessica (2016)
Self-determined political and economic structures can nurture local capacity for adaptive response to a rapidly changing climate and economy. What level of potential for creating such structures is contained within Nunavut’s economic development strategies? In order to explore this topic, this investigation aimed to 1) identify the goals of Nunavut’s economic development strategies, 2) determine whether the goals are currently achievable, and 3) describe how the contents of the economic development strategies compare to what the literature says will produce community wellbeing. The five economic development strategy documents produced by the Government of Nunavut’s Department of Economic Development and Transportation were chosen for analysis. This investigation focused on the challenge of attaining sustainable community economic development within the context of a neo-colonial economic and political regime. A directed content analysis was conducted. This analysis utilized the Harvard Project’s nation-building framework as a foundation and then expanded upon it to represent new themes that emerged from the documents. A second level analysis was undertaken to examine the implementation plans in each strategy. This research produces valuable baseline information regarding current territorial level economic goals and plans, which will influence local capacity for adaptation and self-determination.